A STUDY ON PERCEPTION TOWARDS DIGITAL BANKING SERVICES OFFERED BY INDIA POST PAYMENTS BANK IN TIRUNELVELI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
The digital banking system plays a vital role in commercial banking operations. The fast moving world has driven people to make everything instantly. Hence people want all their transactions to be noted immediately. In the digital world, banking customers can avail of services anywhere in the world. In this regard, the study has branched out its research to know the perception of the product and services offered by India post payments bank (IPPB). Customer has a different perception of the products and services based on their age, domicile, It also to find out what influence the consumer in determining the quality of the product/ services. There are 465 respondents were taken as a sample for the purpose of a perception study of IPPB in Tirunelveli District.